2020
DOI: 10.2174/1389201020666191114104850
|View full text |Cite
|
Sign up to set email alerts
|

Production and Preliminary In Vivo Evaluations of a Novel in silico-designed L2-based Potential HPV Vaccine

Abstract: Background: L2-based Human Papillomavirus (HPV) prophylactic vaccines, containing epitopes from HPV minor capsid proteins, are under investigation as second-generation HPV vaccines. No such vaccine has passed clinical trials yet, mainly due to the low immunogenicity of peptide vaccines; so efforts are being continued. A candidate vaccine composed of two HPV16 L2 epitopes, flagellin and a Toll-Like Receptor (TLR) 4 agonist (RS09) as adjuvants, and two universal T-helper epitopes was designed in silico in our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…More recently, immunization of mice by two epitopic domains (10–36 and 65–89) of HPVL2 fused to flagellin, RS09 and two universal T-helper epitopes was studied. Although preliminary results of this study indicated overall induction of humoral and cellular responses but no specific immune tests were addressed 20 . There are accumulating evidences that the proper combination of several built-in adjuvants (especially TLR agonists) alone or in formulation with external adjuvants might synergistically boost the immune responses against the targeted antigenic peptide 21 , 22 .…”
Section: Introductionmentioning
confidence: 74%
“…More recently, immunization of mice by two epitopic domains (10–36 and 65–89) of HPVL2 fused to flagellin, RS09 and two universal T-helper epitopes was studied. Although preliminary results of this study indicated overall induction of humoral and cellular responses but no specific immune tests were addressed 20 . There are accumulating evidences that the proper combination of several built-in adjuvants (especially TLR agonists) alone or in formulation with external adjuvants might synergistically boost the immune responses against the targeted antigenic peptide 21 , 22 .…”
Section: Introductionmentioning
confidence: 74%
“…HPV is one of the most important carcinogenic viruses in humans. Different HPV serotypes have been discovered, among which HPV-16 and HPV-18 are the most prevalent mucosal high-risk serotypes, associated with nearly 90% of human cervical cancers and 20% of oral cancers 58 60 . The E6 and E7 genes of HPV play a causative role in cancer progression; the former promotes degradation of p53 through its interaction with E6AP , an E3 ubiquitin ligase, while the latter binds to the retinoblastoma protein ( prb ) and disrupts its complex formation with E2F transcription factors so that p53 is suppressed and rb is promoted causing a higher rate of cell division 61 .…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year disease-free and overall survival rates were significantly higher among cervical cancer patients with a high M1/M2 ratio in tumor tissues compared to cases with a low M1/M2 ratio [ 24 ]. In addition, it was reported that elevation of the Th1/Th2 cytokine ratio could increase cellular immunity and prevent the progression of CIN and invasive cervical cancer [ 25 ]. Therefore, it was suggested to develop strategies that promote cellular immune responses, including increasing the Th1/Th2 cytokine ratio, preventing monocyte recruitment to the TME and shifting macrophage phenotypes to M1 macrophages, to prevent the progression of cervical cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 99%